Osteochondroma of talus and coalition of talocrural and intercuneiform joints - surgical management - Keny, Swapnil M.; Sawant, Kaustubh A.; Singh, Vijay; Sharma, Ayush (International Journal of Research in Orthopaedics, 2021)
Osteochondroma of talus is rare benign tumour. Tarsal coalition is a condition in which two or more tarsal bones are joined by non-osseous bridges of cartilage or fibrocartilage or by osseous bridges. Association of Talus osteochondroma with coalition of tarsal bones is extremely rare and has not been reported in the literature before. We are herewith reporting a case of osteochondroma of the talus with coalition of intercuneiform and talocrural joint in an 11-year-old male patient. Patient noticed swelling around ankle and pain on strenuous activities. CT scan confirmed the diagnosis. We did complete extraperiosteal excision of the osteochondroma and resection of tarsal coalition. Histopathological examination confirmed the diagnosis of osteochondroma. At one-year follow-up there is no recurrence of the tumour and patient had full range of motion. Complete extraperiosteal excision of the osteochondroma along with resection of tarsal coalition is important for complete eradication and preventing a recurrence.